UTILIZATION OF FLOWER CARD MEDIA FOR THE INTRODUCTION OF ENGLISH VOCABULARY IN EARLY CHILDHOOD AT POCENTER (PONOROGO EARLY EDUCATION CENTER) - Pradiptya, Isya Nabilah; Kristiana, Dian (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of this research is to identify and obtain information about introduction of English vocabulary in early childhood in Pocenter, how processes in learning activities using flower card media. Data and information is collected through observations and interviews with teachers at the Pocenter. This study explains and gives an overview of the learning activities using the flower card media for the introduction of English vocabulary. The results of this study show that the learning activity of introducing English words to early childhood children using flower cards in its implementation still has many shortcomings and obstacles, but has been implemented optimally. The school also applies pre-learning habits to train the child's concentration to be more focused when learning begins later. Introduction to English vocabulary for children who are at Pocenter is essential because to go to the next level. The media flower card can also develop the child's fine motor aspects, art, creativity, and language.